Pengembangan Modul Ajar Berdiferensiasi Berbasis Media Sosial untuk Meningkatkan Literasi Digital di SMAN 1 Selong - Muhamad Ali Muis; Muhamad Ali; Armin Subhani (Universitas Hamzanwadi, 2026)
This research aims to develop a differentiated teaching module based on social media that meets the criteria of validity, practicality, and effectiveness, in order to improve students' digital literacy skills in learning materials about conflict and violence in high school. This research uses a research and development (R&D) approach as the main method. Module development is carried out through systematic stages based on the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The analysis stage includes the identification of learning needs. The design stage includes the preparation of module frameworks and flows, display design, reference selection, and evaluation instrument design. The development phase includes creation, validation by experts, and revision of modules. The implementation stage is in the form of module trials for students. Meanwhile, at the evaluation stage, the aim is to assess the advantages and disadvantages of the teaching module as a result of the trial. The quality of teaching modules is measured based on three main aspects, namely validity, practicality, and effectiveness. The feasibility of this module was obtained through the evaluation of learning and material planner experts, with a score of 75%, the assessment of media and learning technology experts of 95%, and the results of linguist assessments of 91%. The teaching module was also declared practical based on user feedback by teachers and students by 92%. Based on the results of interviews with teachers and students, as well as referring to the results of post-tests and performance, this teaching module was declared effective in improving students' digital literacy skills in conflict and violence materials. Thus, it can be concluded that the social-media-based differentiated teaching module developed is valid, practical, and effective.